SAT0109 SMOKING CESSATION IN PATIENTS WITH RA IS ASSOCIATED WITH REDUCED CVD EVENT RATES AND IMPROVED LIPID PROFILES AND PREDICTS LOWER RA DISEASE ACTIVITY. (June 2019) - Roelsgaard, Ida Kristiane; Ikdahl, Eirik; Rollefstad, Silvia; Wibetoe, Grunde; Esbensen, Bente Appel; Kitas, George D.; Riel, Piet van; Gabriel, Sherine; Kvien, Tore K.; Douglas, Karen; Jonsson, Solveig Wallberg; Dahlqvist, Solbritt Rantapaa; et al.
Abstract : Background: Smoking is a major risk factor for development of both cardiovascular disease (CVD) and rheumatoid arthritis (RA) and causes an attenuated response to antirheumatic treatment. Objectives: The aim of this study was to compare disease activity and CVD risk factors across smoking status in RA patients. Further to evaluate the impact of smoking cessation on risk of future CVD events in these patients. Methods: RA disease characteristics, CVD risk factors and relevant medication were recorded in patients from 10 countries (Norway, UK, Netherlands, USA, Sweden, Greece, South Africa, Spain, Canada and Mexico). Information on CVD events were collected after a median follow-up of 3.54 years (inter-quartile range 2.51 – 6.06). Adjusted analysis of variance, logistic regression and COX proportional hazards analyses with time to event as response variable were applied to compare RA disease activity (measured by DAS28), CVD risk factors and CVD event rates across current, former and never smokers. Results: Among the 3311 included RA patients (1012 former, 887 current and 1412 never smokers), 235 experienced a CVD event(s) during follow-up. At enrollment into the study current smokers were more likely to have moderate/high disease activity compared to former and never smokers (p<0.001 for both) (Figure 1 ). There was a gradient of worsening CVD risk factor profiles (lipoproteins and blood pressure) from never smokers, via former smokers, to current smokers. Furthermore, after 3.54 years of follow up former and never smokers had significantly lower CVD event rates compared to current smokers (hazard ratio (95% confidence interval): 0.70 (0.51, 0.95), p=0.02 and 0.48, (0.34, 0.69), p<0.001, respectively) (figure 2 ). The CVD event rates for former and never smokers were comparable. Conclusion: We show for the first time that smoking cessation in RA patients was associated with lower disease activity, improved lipid profiles and was a predictor of reduced rates of CVD events. Disclosure of Interests: Ida Kristiane Roelsgaard: None declared, Eirik Ikdahl: None declared, Silvia Rollefstad: None declared, Grunde Wibetoe: None declared, Bente Appel Esbensen Speakers bureau: For Pfizer, George D Kitas Speakers bureau: GDK has received honoraria for lectures, participation in advisory boards and/or hospitality by Roche, Abbvie, Pfizer, Novartis, UCB, BMS, GSK and received grant support from Lilly., Piet van Riel: None declared, Sherine Gabriel: None declared, Tore K. Kvien Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche and UCB., Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Novartis, Oktal, Orion Pharma, Pfizer, Roche, Sandoz, Sanofi, Mylan and UCB, Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Hospira, Merck-Serono, MSD, Novartis, Oktal, Orion Pharma, Pfizer, Roche, Sandoz, Sanofi and UCB, Karen Douglas: None declared, Solveig Wallberg Jonsson: None declared, Solbritt Rantapaa Dahlqvist: None declared, George Karpouzas Grant/research support from: Pfizer, Consultant for: Sanofi-Genzyme-Regeneron, Janssen, Roche-Genentech, Pfizer, Speakers bureau: BMS, Sanofi-Genzyme-Regeneron, Janssen, Roche-Genentech, Patrick Dessein: None declared, Linda Tsang: None declared, Hani El-Gabalawy: None declared, Carol Hitchon: None declared, Virginia Dr. Pascual: None declared, Irazu Contreras-Yáñez : None declared, Petros Sfikakis: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Cynthia S. Crowson: None declared, Anne Grete Semb: None declared